Enhancing damping-like efficiency by low-energy mixed ions bombardment - Bhatti, Sabpreet (2024)
Pursuing enhanced spin-orbit torque (SOT) has become a significant focus for achieving energy-efficient spintronics devices. Researchers have explored different materials, layer engineering, and various post-deposition modification methods to realize higher SOT. Here, we have utilized the bombardment of mixed ions (Ar+ and He+ in various ratios) with 0.6 kV bias voltage to enhance the SOT efficiency in a Pt/Co/W stack. The bombardment modifies the physical properties (magnetic, electric, and structural) due to cascade collision, knocking off atoms (from the surface), and ion implantation. The increased percentage of He+ suppresses the drastic behavior of cascade collisions, and hence, the properties are tunable by changing the gas ratio. We exploited this behavior to design a material stack with enhanced SOT efficiency. We fabricated Hall bars to quantify SOT and observed a 4.5× increase in the effective damping-like efficiency. The efficiency and switching current density in the stack could be tuned by the variation of Ar:He ion ratio and the exposure duration. This study offers an easy route to tune the energy efficiency of spin devices, contributing to the advancement of next-generation spintronics.